Fortifying Life Skills and Family Guardianship at the “KAMPUS BUNDA” Literacy Hub - Saputri, Yulian Zhafirah Aji; Zain, Kurnia Salsabila; Mubarokah, Kismi; Suryawijaya, Tito Wira Eka; Rahmadani, Aulia Fajrin; Nurlaely, Kharisma (Universitas Lambung Mangkurat, 2024)
Inisiatif